Tetanus Toxoid Immunization Status and Associated Factors among Mothers in Damboya Woreda, Kembata Tembaro Zone, SNNP, Ethiopia - Muluken Dubale Mamoro; Lolemo Kelbiso Hanfore (Journal of Nutrition and Metabolism)
Background. Tetanus toxoid immunization is one of the proven strategies for eliminating maternal and neonatal tetanus. According to Ethiopian Demographic Health Survey of 2016, only 49% of mothers received two tetanus toxoid (TT) injections during their last pregnancy which is below the World Health Organization and Ethiopia Ministry of Health recommendation. Therefore, the aim of this study was to determine the status of TT immunization among mothers in Damboya Woreda, South Ethiopia. Method. A community-based cross-sectional study was conducted from March 1 to 26, 2017, in Damboya Woreda. A total of 837 mothers who had given birth in the last 12 months were included in the study. The simple random sampling method was used to select the study participants, and data were collected through an interview using a structured questionnaire. Data were entered into Epi data software version 3.1 and exported to SPSS version 22 for further analysis. Logistic regression was used to identify independent predictors of the immunization status of mothers at a 5% significance level. Result. The finding of this study revealed that 607 (72.5%) mothers were protected at birth against tetanus. Age of mother who attended elementary school, husbands’ education status, visited by HEW’s at home, making joint health decision with husband, use of modern family planning method, number of antenatal care visit, and time to reach the nearest health facility were independent predictors of TT immunization status among the mothers. Conclusion. Significant proportions of the mothers were not taken at least two doses of TT vaccine which is a minimum dose to prevent maternal or neonatal tetanus. Even though most mothers had access for TT immunization service, they were not immunized with protective doses of TT vaccine.